Effects of Initial Shear Stress and Vibration Frequency on the Dynamic Pore-Water Pressure of Saturated Sands - Jian Zhang; Jiuting Cao; Sijie Huang (Advances in Civil Engineering)
The cyclic triaxial system is used to investigate the effects of confining pressure, initial shear stress, vibration frequency, and dynamic stress on the pore-water pressure characteristics of saturated sand in the Wenchuan area. Results show that the initial shear stress has a remarkable effect on the development of the dynamic pore-water pressure of saturated sand. The greater the initial shear stress, the slower the development curve of the pore-water pressure of saturated sand and the higher the number of cycles required to reach the same pore-water pressure. The larger the initial shear stress, the smaller the dynamic pore-water pressure when the sample is destroyed. Moreover, the maximum pore-water pressure ratio decreases linearly with the increase of the consolidation ratio. The normalised relationship curve between the dynamic pore-water pressure and failure time of vibration is consistent with the development law of the power function. The power function model parameters are affected by the initial shear stress and confining pressure. At the time of isotropic consolidation, the accumulation law of pore-water pressure presents a growth pattern of “fast-stable-intensified.” A modified pore-water pressure model considering vibration frequency is proposed on the basis of the Seed pore-water pressure model, and the model parameters are linear with the vibration frequency. When the vibration frequency remains unchanged, the parameter does not change with the confining pressure and dynamic stress. This modified model can predict the change rule of pore-water pressure with the frequency under isotropic consolidation.